Gold Catalysed Redox Synthesis of Imidazo[1,2-a]pyridine using Pyridine N-Oxide and Alkynes - Talbot, Eric P. A. (2014)
A mild, catalytic, atom economical synthesis of imidazo[1,2-a]pyridines has been developed: catalytic PicAuCl(2) in the presence of an acid produces a range imidazo[1,2-a]pyridines in good yield. This strategy is mild and forseen to be of particular use for the installation of stereogenic centers adjacent to the imidazo[1,2-a]pyridine ring without loss of enantiomeric excess.